The Experimental Study of the Effect of Glass and Carbon Fiber on Physical and Micro-Structure Behavior of Asphalt - Khabiri, Mohammad Mehdi; Alidadi, Majid (International Journal of Integrated Engineering, 2017)
Performance failures in asphalt pavements, which are related to the use of traditional asphalt materials has made pavement scientists to adopt new strategies in utilizing new materials in pavement industry. Some of additive materials are like fiber or yarn including natural and synthetic fiber such as glass and carbon fiber. These materials reinforce the mix and cause increase in tensile strength. In this study, two yarn types were chosen to investigate on; namely, glass and carbon. The aim of this study was to investigate the properties of reinforced asphalt mixtures with carbon and glass fibers. To evaluate the effect of carbon and glass fibers on asphalt mixtures physical performance, Marshal Stability and indirect tensile tests were carried out according to international standards on the samples with and without fibers through the dry method. The results of study showed that fiber glass had greater effect on increasing rutting resistance and increase the percentage of glass fiber in the mix which causes to increase the ratio of Marshall and in other words cause to rutting reduction. The results also indicated that the behavior of fracture for fibrous samples were somewhat different from fracture of non-fibrous samples and does not create a manifest failure screen. Examining indirect tensile strength samples, constructed of optimal fiber percentages were obtained for glass fiber and carbon fiber content of 2% and of 3%, respectively. Results also showed that adding fiber to mixtures resulted in increased length of failure screen.Â Â